Prospective study to correlate the level of glycosylated haemoglobin with wound healing, vasculopathy and neuropathy in diabetic foot patients - Kumar, Brajkishor; Mishra, Manish Kumar; Sinha, Ajit; Soni, Rajesh Kumar; Patel, Dharmendra Kumar (International Surgery Journal, 2016)
Background: Diabetes mellitus is a prevalent global health problem and diabetic foot represents one of its dreadful complications. Early aggressive approach and multidisciplinary intervention prevent limb loss and disease fatality. Glycosylated haemoglobin (HbA1c) reflects long term glycaemic control and helps in prediction of complications as well as response to treatment. Methods: A total of 50 patients with diabetic foot ulcer (Wegner grade 1, 2) made nucleus of this study. Every patient underwent proper clinical, hematological and sonological assessment. Optimum treatment was provided and the effect of improvement in HbA1c value was correlated with duration of wound healing, vasculopathy and neuropathy over a 12 week follow uu. Results: Mean age of presentation was 53.4 years and patients developed diabetic ulcers (Wegner grade 1, 2) at a mean HbA1c value of 6.6. Foot trauma was inciting event in 70% cases. 70% patients had neuropathy and 30% had vasculopathy at presentation. Mean duration of healing was 42.6 days. Healing was faster in the group with lower HbA1c; however there was no improvement in neuropathy or, vasculopathy in 12 weeks duration. Conclusions: Based on the observations of present study it may be submitted that lower HbA1c value contributes to faster wound healing, however it doesn’t improve neuropathy and/or vasculopathy over duration of 12 weeks.